Bubble Free Electrodes for Electroosmotic Pumping - Subramani, Ganapathy Balasubramanian (My University, 2007)
Electroosmotic (EO) pumping is a widely used micro fluidic pumping technique due to its advantages such as simple design, applicability to wide range of conductive fluids and favorable scaling of electrical forces. Electrodes are necessary to establish the electrical forces and hence fluid flow inside the micro channel. One of the major problems associated with inert electrodes such as gold or platinum used in EO pumping is gas evolution, whereas redox electrodes have a shorter life time. In this thesis, EO pumping is demonstrated using two different bubble free electrodes with longer lifetime.
The first of the two types demonstrated is thick silver/ silver chloride electrodes embedded in poly di-methylsiloxane (PDMS) micro channels. However, embedding thick electrodes inside PDMS channels using traditional micro fabrication will lead to a gap near the electrodes which can result in leakage of the working fluid. A new surface micromachining technique in PDMS has been developed to address the leakage problem.
Surface micromachining with PDMS as a structural material and photoresist as a sacrificial material allows the fabrication of PDMS microchannels on substrates with significant topography. Adhesion of the structural layer with the substrate is characterized for different prepolymer ratios using standard tensile test. 1:3 (curing agent: base) combination was found to have the highest bonding strength with an adhesion strength of7.2 MPa. The effectiveness of this technique is demonstrated by the fabrication of microchannels with embedded 61lm thick silver/ silver chloride electrodes. The micro channels are leak proof and conformal contact between the PDMS and electrode is confirmed through SEM. The release time for micro channels was reduced to 1 min irrespective of the length of the micro channel. The flexibility and versatility of this technique for fabrication of multi layered micro channel structure is demonstrated through a micro fluidic valve. The valve closure occurred at 6.37 kPa.
The Voltage-current density of the Ag/AgCl electrodes was characterized. The limiting current density of the electrode is 2.7 mAlcm2. The capacity of the electrodes is 1680 μA-sec. EO pumping has been demonstrated with an applied voltage of 1-2 V and a maximum velocity of 44 μm/sec is obtained.
The second bubble free electrode demonstrated is an inert liquid electrode which has an extended life unlike the metal electrodes. The device consists of two upper PDMS micro channels and a lower micro channel with a 6μm thick nanoporous polycarbonate sheet placed in between them. An electro osmotic pump has been demonstrated using this liquid electrode configuration with a maximum velocity of 118 μm/sec at 60 V.
Keywords: Mechanical Engineering; Mechanical Engineering